Residential Landscapes Sponsored by Companhia União Fabril (CUF) in Barreiro (1945-1972). Promotion of Multi-Family Working-Class Housing in Post-WWII Portugal - Ana Vaz Milheiro; João Cardim (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article deals with the promotion of housing for the working class in Portugal after World War II. The starting point of the research is the strategies followed by Companhia União Fabril (CUF) — a major Portuguese chemical company — between 1945 and 1972 in Barreiro, a town on the southern bank of the Tagus River, where the company had been gradually establishing its main factory grounds since the beginning of the twentieth century. The article argues that the publication of Law no. 2092 of April 9th 1958, which called upon welfare institutions to provide answers to the housing problem, was a fundamental step in the transformation of the Portuguese urban, suburban and rural environment, with massive consequences that historiography has yet to fully address.The article identifies the workers’ neighborhoods built by the company on factory grounds (1908-1946), comparing them to those that were later built on suburban farms (1951-1956), destined not only for the traditional working class, but also a growing middle-class that was emerging among the company’s staff. It then describes the operations that were carried out after the publication of the aforementioned law, between 1958 and 1967, and its repercussions up until the eve of the 1974 April Revolution. This law is essentially seen as positive, and had significant results in fighting the housing shortage issues of the time. However, we argue that it also shifted the housing provision responsibilities from private actors — in this case CUF — to public ones, leading to a fragmented urban landscape where the changes over the course of history — in terms of legislation, urban planning, architecture and social fabric — can be witnessed firsthand.